Seismic Performance Analysis for an Eccentrically Braced Frame (EBF) with an Innovative Self-Centering Shear Link - Xinyu Xu; Lifen Huang; Shangwen Liu; Bo Zhang; Shujun Hu (Buildings)
By integrating a very short shear link–shear slotted bolted connection (VSSL-SSBC) and two self-centering SMA braces (SCBs), a novel self-centering shear link (SC-SL) was developed for installation between a steel brace and steel beam in an eccentrically braced frame (EBF). The SC-SL can enhance the seismic performance and seismic resilience capacity of the EBF by achieving a high bearing capacity and low residual deformation. The mechanical properties of the VSSL-SSBC and SC-SL were designed and analyzed using both experimental and numerical methods. Subsequently, the seismic performances of EBFs equipped with VSSL-SSBC and SC-SL were analyzed under different earthquakes. Validated numerical methods were employed to investigate the deformation modes, stress nephograms, and hysteresis curves of the EBFs. The deformation mode and hysteresis curve of the VSSL-SSBC exhibit an initial frictional slip of the SSBC, followed by the load-bearing response of the VSSL. The skeleton curve of the VSSL-SSBC consists of elastic, slip, elastoplastic, and plastic stages, and the deformation and damage are significantly reduced at the same displacement. In the SC-SL, the SCB undergoes substantial deformation when the SMA is in tension, effectively minimizing residual deformation. Under frequent earthquakes, the stress and displacement of all components in both the EBF-VSSL-SSBC and EBF-SC-SL are essentially equivalent, and the VSSL-SSBC remains elastic, without significant yielding deformation. Under rare earthquakes, incorporating SCB in EBF-SC-SL significantly enhances the ultimate load capacity by 19.66% and reduces the residual deformation by 27.90%. This improvement greatly contributes to the seismic resilience of the EBF.